Serotonin Syndrome Following Combined Administration of Dopaminergic and Noradrenergic Agents in a Patient With Akinetic Mutism After Frontal Intracerebral Hemorrhage: A Case Report - Jeon, Dae Geun; Kim, Yong Wook; Kim, Na Young; Park, Jung Hyun (Clinical neuropharmacology, 2017)
Serotonin syndrome (SS) is a potentially life-threatening condition that can be caused by use of proserotonergic drugs. Several studies have reported that combined administration of various medications may induce SS. We report a case of SS in a patient who was being treated with dopaminergic and noradrenergic drugs. A 55-year-old man with a right frontal intracerebral hemorrhage extending to the left cerebral hemisphere presented with clinical features of akinetic mutism. Three months after onset, dopaminergic (methylphenidate, levodopa/benserazide) and noradrenergic (atomoxetine) drugs were administered to enhance his cognitive function. His cognitive function gradually improved during 8 weeks of dose escalation. One day after the dose of atomoxetine was increased from 40 mg/d to 60 mg/d, the patient developed inducible clonus, rigidity, diarrhea, tachycardia, and hyperthermia, in keeping with a diagnosis of SS. The symptoms and signs suggestive of SS resolved on the day following cessation of all dopaminergic and noradrenergic drugs. This case demonstrates that medications generally known as dopaminergic or noradrenergic agents could have serotonergic effects via a mechanism that is yet to be fully elucidated. The clinical manifestations of SS can be diverse, ranging from mild to severe and potentially fatal symptoms. When administering a combination of catecholaminergic agents, clinicians should carefully monitor the patient's neurologic status for unexpected adverse reactions.